Concepts and criteria for assessing the technological independence and security of critical information infrastructure facilities - Boris N. Krivoshein; Ivan A. Pokrovsky (Безопасность информационных технологий, 2023)
The article presents an analysis of the concepts and terms used in the Decree of the President of the Russian Federation No. 166 dated 30.03.2022 "On measures to ensure the technological independence and security of the critical information infrastructure of the Russian Federation". Differences in the concepts of technological sovereignty and security of infrastructure facilities are identified, as well as differences between the criteria for assessing the trust of software and hardware complexes and the criteria of Russian origin. Clarifications of the regulatory framework are proposed, which will eliminate discrepancies in concepts and contradictions in requirements.